Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematika Peserta Didik Kelas IX SMP Negeri 4 Sutera Kab. Pesisir Selatan - WIWY PRATAMA PUTRI (Departemen Matematika, 2019)
Understand mathematical concepts ability is the main goal in learning mathematics. This means that understanding mathematical concepts is a major point in achieving other mathematical goals. This study aims to determine whether understand mathematical concepts ability using Student Teams Achievement Division (STAD) cooperative learning models better than understand mathematical concepts ability using direct learning models. This research was conducted at SMP Negeri 4 Sutera Kab. Pesisir Selatan, Padang, 32 students in the experimental class and 32 students in the control class. This type of research is quasy experiment with the Static Group Design research design. The results showed that understanding of mathematical concepts using the STAD learning model had increased. It can be concluded that understand mathematical concepts ability using the Student Teams Achievement Division (STAD) cooperative learning model is better than understand mathematical concepts ability using the direct learning model. Keywords — Cooperatif Learning, Mathematical Concept, STAD Learning Model.